1997
DOI: 10.1076/phbi.35.3.174.13294
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Cytotoxic Properties of Some Malaysian Traditional Vegetables (Ulam)

Abstract: Ethanol extracts of 19 Malaysian traditional vegetables (locally known as 'ulam')

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
1
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 6 publications
1
75
1
4
Order By: Relevance
“…Ethanol extract of the leaves of E. elatior showed activity against bacteria gram-positive (Bacillus cereus and Bacillus megatrium) and bacteria gram negative (Escherichia coli and Pseudomonas aeruginosa). The results revealed that E. elatior showed antibacterial activity with minimum concentration 100-800 mg/mL and the minimum lethal concentration 400-800 mg/mL [6]. In addition, E. elatior had antibacterial activity against S. aureus with minimum inhibitory concentration values about 15% of concentrations at with the percentage of inhibition about 95.63%, E. coli by 50% with the percent inhibition of 92.41%.…”
Section: Introductionmentioning
confidence: 72%
“…Ethanol extract of the leaves of E. elatior showed activity against bacteria gram-positive (Bacillus cereus and Bacillus megatrium) and bacteria gram negative (Escherichia coli and Pseudomonas aeruginosa). The results revealed that E. elatior showed antibacterial activity with minimum concentration 100-800 mg/mL and the minimum lethal concentration 400-800 mg/mL [6]. In addition, E. elatior had antibacterial activity against S. aureus with minimum inhibitory concentration values about 15% of concentrations at with the percentage of inhibition about 95.63%, E. coli by 50% with the percent inhibition of 92.41%.…”
Section: Introductionmentioning
confidence: 72%
“…Antibacterial assay using a disc diffusion method Antibacterial activity was measured using a disc diffusion method described by Mackeen et al [21]. Standard antibiotic, streptomycin was used as positive control.…”
Section: Qualitative Analysis Of Secondary Metabolitesmentioning
confidence: 99%
“…(Piracicaba, Braz. ), v.68, n.1, p.69-76, January/February 2011 are used to treat cough, asthma and diarrhea and the seeds for treatment of colic, jaundice and ophthalmic disorders (Behbahani et al, 2007b;Khan et al, 2000;MacKeen et al, 1997). The bark ethanol extract has antitumor property in mice (Khan et al, 2000), but the leaf ethanol extract displayed cytotoxicity against the HelA (human cervical carcinoma) cell lines with IC 50 value of 10 μg mL -1 (MacKeen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%